Unreliability of tritiated cholesterol: studies with [1,2-3H]-cholesterol and [24,25-3H]cholesterol in humans. - Davidson, N O (1980)
Over the past 18 months different lots of [1,2-3H]cholesterol and [24,25-3H]cholesterol were found to be radiochemically acceptable by conventional chemical and other in vitro tests, yet, when co-administered with [4-14C]cholesterol to human subjects, an abrupt fall in the 3H/14C specific activity ratio in plasma cholesterol was discovered in every case. We have concluded that all batches of [3H]cholesterol should be regarded as radiochemically unreliable unless they are shown to behave identically in all respects to [4-14C]cholesterol in an appropriate in vivo assay system.